(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
"amortecido" is a work developed in the pedagogical process of the discipline of Theater Editing I and II - 2023, in the undergraduate course in Theater at the Arts Center of the State University of Santa Catarina (UDESC), taught and directed by Zilá Muniz with a class of 17 students.